Women's Entrepreneurship in Rural India: An Essential Factor in the Development of the Indian Economy: Exploring the Challenges and Opportunities for Women Entrepreneurs in Rural India (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Entrepreneurship entails using one's own judgement to determine when and where new formsof economic activity could be developed. According to the 2020 census, women made up 68.6 percentof India's population and their literacy rate rose from 54.28 to 65.46.Women are the key to aprosperous country. Women business owners in today's mostly male-dominated culture require moreaccess to educational and professional development opportunities to establish their worth. Male is thedefault gender in our culture, while female is a secondary option. My research focuses on the businesspossibilities and threats faced by women in the Hyderabad Telangana Region in the India. Women nowcompete equally with men in all fields. This study drew heavily on both primary and secondary data. Anation's economic success in today's linked globe depends on women's participation in ruraldevelopment. The subject of women starting their own businesses in India's rural communities is afresh one.A woman entrepreneur is someone who, in order to meet her own needs and build financialsecurity, seeks out and accepts hard tasks. Women account for over eight million of India's companyowners, with the region of Hyderabad Telangana boasting the highest number. This is based on datagathered from several external resources, including books, academic articles, websites. The future ofwomen business owners is explored, as well as government initiatives aimed at fostering their success.The study reveals a few approaches to elevating rural women's status.